2020
DOI: 10.1093/workar/waaa023
|View full text |Cite
|
Sign up to set email alerts
|

The Use of HR Policies and Job Satisfaction of Older Workers

Abstract: Against the backdrop of aging populations and policies to extend working lives, this study advances prior research by examining how job satisfaction of older workers is associated with not only own, but also coworkers’ usage of 3 human resource (HR) policies: phasing out (i.e., lighter workload, additional leave, and semi-retirement), demotion, and training. Exploiting unique, linked organization-department-employee data from the European Sustainable Workforce Survey (ESWS), hypotheses derived from the job dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…This paper provides some of the first empirical analysis of job satisfaction among a sample of healthcare workers, with a specific focus on the interaction of age and certain key job-related attitudes. While other research has investigated the antecedents of work satisfaction across the wider workforce (Zhu et al, 2021) and of factors specific to older workers' satisfaction (Visser et al, 2020), we are not aware of previous work that specifically investigates the relative importance of job (in)security on work satisfaction and how these change with age.…”
Section: Older Healthcare Workers' Satisfaction 319mentioning
confidence: 96%
“…This paper provides some of the first empirical analysis of job satisfaction among a sample of healthcare workers, with a specific focus on the interaction of age and certain key job-related attitudes. While other research has investigated the antecedents of work satisfaction across the wider workforce (Zhu et al, 2021) and of factors specific to older workers' satisfaction (Visser et al, 2020), we are not aware of previous work that specifically investigates the relative importance of job (in)security on work satisfaction and how these change with age.…”
Section: Older Healthcare Workers' Satisfaction 319mentioning
confidence: 96%
“…Although managers believe that demotion could be a fair reaction in the case of older employees' missing motivation and related performance drops, they typically shy away from this practice due to potentially negative staff reactions (van Dalen & Henkens, 2018). They are probably right with this assumption as Visser et al (2021) demonstrated that demotion shows a negative relationship with older employees' job satisfaction while this is not the case for phasing-out arrangements. Finally, we want to turn to organizational policies fostering retention and worklife extension versus offering exit policies.…”
Section: Individual Dimensions Of Age-related Hrm Practicesmentioning
confidence: 99%
“…The second study at the meso-level of analysis is Visser et al (2021). These authors are also interested in the role of individual HR-practices for older workers, particularly phasing out (e.g., lighter workload or semi-retirement), demotion and training.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Instead, it may be better if organizations continue to provide older workers with activating workdays (with high work pressure and autonomy), which will promote their work engagement and performance (Kooij et al 2020 ). Also, organizations could apply an HR policy that emphasizes older workers’ participation in training rather than their phasing out (e.g., lighter workload, semi-retirement), or demotion (movement to a less demanding position) as only training was found to promote job satisfaction (Visser et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%